THE ANALYSIS OF FOREIGN DIRECT INVESTMENT TRENDS AND STATE OF DEVELOPMENT OF THE M&A MARKET OF GAS&OIL COMPANIES - F. Garifullin (Вестник университета, 2019)
This article presents the results of dissertational research which suggests that most M&As in Russia’s gas & oil sphere fall to countries of Asia Pacific region that are the most promising not only in terms of strengthening the political ties but also for promoting economic cooperation by means of attracting foreign direct investment and concluding M&A deals. The decrease of transactions volume of purchase of Russian assets by European and North American companies are the result of expanding and toughening the sanctions against Russia. At the same time, significant share of direct foreign investments in 2015 was received from jurisdictions with preferential taxation orders. It is to be noted that given jurisdictions are most likely not the initial sources of investments.